Chronic Obstructive Neutrophilic Cholangiohepatitis Associated with Bacteremia in a Cat - Resende, Isa Lúcia Sousa; Paixão, Polyana Pulcheira; Ana Flávia Silva Pereira; Hugo Henrique Victorino Victório; Stefani Fernandes de Souza; Beatriz Aline Migotto; Anna Luiza Alves Miranda; Claudine Botelho de Abreu (Acta Scientiae Veterinariae, 2025)
Background: Cholangiohepatitis is an inflammatory disease of the bile ducts that affects the adjacent liver parenchyma, leading to symptoms such as anorexia, jaundice, vomiting and apathy in felines. Obstruction of the bile ducts due to extrahepatic cholestasis can significantly compromise digestion and nutrient absorption. This present report describes a case of obstructive neutrophilic cholangiohepatitis associated with bacteremia in a cat, highlighting the diagnostic challenges, therapeutic strategies and the prognosis of this complex disorder. Case: A 11-year-old female cat Brazilian shorthair breed, weighing 3.8 kg, was attempted. The animal presented vomiting, hyporexia and jaundice. The blood count revealed normocytic normochromic anemia and neutrophilia with regenerative left shift. The biochemical analysis showed an increase in gamma glutamyltransferase (GGT). Abdominal ultrasound demonstrated changes suggestive of obstructive cholangiohepatitis. Clinical treatment with antibiotics, choleretics, hepatoprotectors, immunosuppressants and antiemetics was instituted. In order to restore bile flow, a cholecystoduodenostomy was performed. Bile culture demonstrated growth of aerobic Proteus sp. Liver biopsy revealed chronic suppurative cholangitis with foci of fibrosis, establishing the diagnosis of obstructive neutrophilic cholangiohepatitis. Due to worsening disorder, a blood culture was performed, identifying Enterococcus sp. Antibiotic therapy guided by antibiogram resulted in the improvement of the clinical condition. Discussion: Throughout all stages of cholangiohepatitis, hyperbilirubinemia and elevated levels of liver enzymes such as alanine aminotransferase (ALT), aspartate aminotransferase (AST), alkaline phosphatase (ALP) and GGT are commonly observed. A diagnosis of cholangiohepatitis is challenging and often requires a multifaceted approach. In that case, a combination of laboratory tests (complete blood count and liver enzymes) and imaging methods (abdominal ultrasound) was crucial for identifying hepatic changes and bile duct obstruction. Liver biopsy was essential to confirm the neutrophilic nature of the inflammation. Bile culture identified bacteremia, directly influencing the choice of appropriate antibiotic therapy. Treatment of this disorder involves an integrated approach. Initially, a clinical protocol was instituted including antibiotics to control bacteremia, choleretics to improve bile flow, hepatoprotectors to protect the inflamed liver, immunosuppressants to control the inflammatory response and antiemetics to alleviate gastrointestinal symptoms. The decision for surgical intervention with cholecystoduodenostomy was necessary to restore bile flow and improve the clinical condition of the animal. The prognosis for obstructive neutrophilic cholangiohepatitis in cats is guarded, especially when complicated by bacteremia and sepsis. The previously described high post-surgical mortality rate, even with appropriate surgical intervention and antibiotic therapy, underscores the challenges associated with managing this condition. However, it is important to note that some patients, like the cat in this report, may achieve positive recovery outcomes with intensive and appropriate management, including targeted antibiotic therapy and continuous clinical support. In conclusion, this case emphasizes the importance of a comprehensive diagnostic and therapeutic approach to feline cholangiohepatitis. Keywords: chronic vomiting, biliary system, cholestasis and obstruction. Título: Colangiohepatite neutrofílica obstrutiva associada à bacteremia em um gato Descritores: vômito crônico, sistema biliar, colestase e obstrução.